Medicamentul Veterinar, la 13 ani de activitate - Valer Teusdea (Medicamentul Veterinar, 2019)
The evolution of 13 years of the Journal Mediciamentul Veterinar is presented by the executive president of The Romanian Association of Veterinary Use Products Manufacturers